Drug treatment for cancer of the corpus uteri: Protracted stagnation or breakthrough expectation - E. V. Artamonova (Опухоли женской репродуктивной системы)
The paper considers the specific features of the course and therapy of cancer of the corpus uteri on the basis of some clinical and biological characteristics of the tumor. The objective of ongoing and future clinical trials is to expand the arsenal of active drugs and to individualize therapy in patients with endometrial cancer.